The dynamics of three shrub species in a fire-prone temperate savanna: the interplay between the seed bank, seed rain and fire regime - Galindez, Guadalupe; Ortega Baes, Francisco Pablo; Scopel, Ana Leonor; Hutchings, Michael J. (Springer, 2018)
A model was developed to assess how the seed rain and fire regime affect seed bank dynamics and seedling establishment of three native shrub species (Acanthostyles buniifolius, Baccharis pingraea and Baccharis dracunculifolia) with different regeneration strategies, in temperate South American savanna. Seed bank and seed rain were quantified for each species under different fire regimes, and their relative roles in regeneration were evaluated. All species had short-term persistent seed banks and high annual variability in seed production. A high proportion of seeds deposited in the seed rain produced seedlings after fire; few entered the soil seed bank. Fire killed a high proportion of the seeds in the soil seed bank. Seedlings derived from the seed rain had a higher probability of surviving for 2 years than seedlings emerging from the soil seed bank. In the absence of fire, establishment depended on germination both from the seed rain and the soil seed bank, whereas with annual fire, establishment was primarily dependent on germination of seeds arriving in the annual seed rain, regardless of species’ regeneration strategies. These results help to explain changes in the vegetation of South American temperate savannas as a result of changes in fire regime and grazing management during the last 50 years. By revealing the crucial roles of the soil seed bank and seed rain in regeneration, this study provides vital information for the development of appropriate management practices to control populations of shrub species with different regeneration strategies in South American temperate savannas.